Case report: IORT as an alternative treatment option for breast cancer patients with difficulty staying still - Bhimani, Fardeen; McEvoy, Maureen; Chen, Yu; Gupta, Anjuli; Pastoriza, Jessica; Fruchter, Shani; Bitan, Zachary C.; Tomé, Wolfgang A.; Mehta, Keyur; Fox, Jana; Feldman, Sheldon (Frontiers in Oncology, 2024)
BackgroundAdministering radiation therapy to individuals with intellectual disabilities (ID) and psychiatric patients taking antipsychotics poses challenges, especially with whole breast irradiation (WBI) due to difficulty staying still (DSS). In such scenarios, intraoperative radiotherapy (TARGIT-IORT) provides an alternative. Although prior studies have shown its applicability in special cases where WBI may be contraindicated, there is a paucity of literature emphasizing its role in patients with ID and psychiatric conditions who have DSS. Therefore, our case series aims to highlight the applicability of administering TARGIT-IORT in such patients.Case reportsFour breast cancer patients underwent lumpectomy and TARGIT-IORT. Among them, two patients had ID, with one experiencing a decreased range of motion. The other two had psychiatric disorders, including schizophrenia and bipolar disorder, both manifesting involuntary movements and DSS. Three patients had invasive ductal carcinoma (IDC), and one had invasive lobular carcinoma (ILC). All patients undergoing TARGIT-IORT tolerated the procedure well. Notably, none of the patients exhibited evidence of disease on follow-up.ConclusionOur study underscores the potential use of TARGIT-IORT as a viable treatment option for breast cancer patients with intellectual and psychiatric disabilities. Unlike traditional EBRT, TARGIT-IORT offers a single radiation dose, addressing challenges associated with compliance or DSS. Our findings demonstrate positive outcomes and tolerance, especially in patients where standard oncologic procedures are difficult to achieve. TARGIT-IORT could also benefit breast cancer patients with concurrent movement disorders like Parkinson’s disease and other movement disorders. Nonetheless, future studies are needed to reinforce its applicability for patients with DSS.